The role of interleukin-19 in diabetic nephropathy - Khaled A Elhefnawy; Ahmed M Salah; Hanaa H Elsaid (SpringerOpen, 2019)
Background Proinflammatory cytokines play an important role in the establishment of arteriolosclerosis and kidney injury. Inflammatory cytokines are involved in the development of microvascular diabetic complications, including diabetic nephropathy (DN). Interleukin-19 (IL-19) has vital functions in many inflammatory processes and also can induce the angiogenesis of endothelial cells. Objective To investigate the role of IL-19 in the development of DN. Patients and methods A total of 112 participants were included and classified into four main groups: group I was the control group, which included 28 age-matched and sex-matched persons; group II included 28 patients with type 2 diabetes without nephropathy (normoalbuminuria); group III included 28 patients with type 2 diabetes with nephropathy (microalbuminuria); and group IV included 28 patient with type 2 diabetes with nephropathy (macroalbuminuria). All participants were subjected to complete blood count, complete urine analysis, fasting and random blood glucose, glycosylated hemoglobin (HbA1c), serum creatinine and urea, urinary albumin excretion rate (UAE), albumin-creatinine ratio (ACR), lipid profile, and serum IL-19 level assays. Results C-reactive protein (CRP) and serum IL-19 levels were significantly higher in diabetic patients compared with controls. IL-19 levels were significantly positively correlated with serum creatinine, ACR, UAE, HbA1c, and CRP. Multivariable logistic regression analysis showed that IL-19 levels were independently associated with patients with DN. Conclusion IL-19 levels were elevated in patients with DN and were positively correlated with ACR, UAE, HbA1c, and CRP. IL-19 may play an important role that contributes to the progression of DN.